Analisa Kinerja Simpang Tiga Tak Bersinyal (Studi Kasus Jalan Raya Sekarpuro - Jalan Raya Ki Ageng Gribig - Jalan Wisnuwardhana Kecamatan Pakis, Kabupaten Malang) - Yolan , Yohanes; Arifianto , Andy Kristafi; Rahma , Pamela Dinar (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2023)
Defined there are several problems that often occur and that are the cause of traffic congestion at the intersection of three unsignalized Jalan Raya Sekarpuro - Jalan Raya Ki Ageng Gribig - Jalan Wisnuwadhana Pakis District, Malang Regency The congestion that occurs is caused by long lines of vehicles due to the presence of large vehicles passing through the intersection of three unsignalized Jalan Raya Sekarpuro - Jalan Raya Ki Ageng Gribig - Jalan Wisnuwadhana. The large flow of vehicles passing through the unsignalized triple intersection of Jalan Raya Sekarpuro - Jalan Raya Ki Ageng Gribig - Jalan Wisnuwadhana where the width of the road is not balanced with the traffic flow. The number of activities on the shoulder of the road such as parking vehicles on the shoulder of the road and there are also street vendors that affect the performance at the intersection of three unsignalized Jalan Raya Sekarpuro - Jalan Raya Ki Ageng Gribig - Jalan Wisnuwadhana. From the results of the analysis of existing conditions at the intersection, it is known that the value of vehicle volume in the first week is 11449,5 skr / hour. The performance of the intersection can be seen from the results of data processing using the Indonesian road capacity guidelines PKJI 2014 at the intersection of three unsignalized the highest degree of saturation (DJ) value is in the first week of Monday morning peak hour is 1.0> 0.85, then it is included in the level of service criteria F, namely the state of the flow persists or there is a long queue of vehicles with low capacity, the volume is below capacity and forms a series of vehicles, congestion often occurs and the time is long enough. In extreme circumstances speed and volume can drop to zero.